2020
DOI: 10.1371/journal.pone.0228882
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported willingness to share political news articles in online surveys correlates with actual sharing on Twitter

Abstract: There is an increasing imperative for psychologists and other behavioral scientists to understand how people behave on social media. However, it is often very difficult to execute experimental research on actual social media platforms, or to link survey responses to online behavior in order to perform correlational analyses. Thus, there is a natural desire to use selfreported behavioral intentions in standard survey studies to gain insight into online behavior. But are such hypothetical responses hopelessly di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
103
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 130 publications
(111 citation statements)
references
References 21 publications
7
103
0
1
Order By: Relevance
“…Participants were randomly assigned to either judge each headline's veracity (Accuracy condition) or indicate if they would consider sharing each headline online (Sharing condition). Although these sharing decisions are hypothetical, research suggests that selfreport sharing decisions of news articles like those used in our study correlate strongly with actual sharing on social media 18 . For full methodological details and explanations of preregistrations for all studies, see Supplementary Information (SI).…”
mentioning
confidence: 62%
“…Participants were randomly assigned to either judge each headline's veracity (Accuracy condition) or indicate if they would consider sharing each headline online (Sharing condition). Although these sharing decisions are hypothetical, research suggests that selfreport sharing decisions of news articles like those used in our study correlate strongly with actual sharing on social media 18 . For full methodological details and explanations of preregistrations for all studies, see Supplementary Information (SI).…”
mentioning
confidence: 62%
“…Thus, laboratory-style data provide a useful window into the potential effects of interventions aimed at fighting misinformation. This is particularly true given evidence that self-reported social media sharing intentions are predictive of actual sharing on social media (Mosleh et al 2019). Nonetheless, it is our hope that future work will be able to explore the issues raised here in the context of more typical social media use.…”
Section: Concluding Discussionmentioning
confidence: 89%
“…(response options: no, yes). We note that although these sharing decisions were hypothetical, there is reason to believe that participant responses shed light on actual sharing behavior on social media: across a set of political news headlines, Mosleh et al (2019) find that self-reported sharing intentions collected on Mechanical Turk are strongly correlated with the number of tweets and retweets a given headline actually received on Twitter.…”
Section: Study 2: Implied Truth and Social Media Sharingmentioning
confidence: 89%
“…Our main dependent variable was belief in several news stories as well as willingness to share these stories on social media. Recent work suggests that the same news headlines that were more likely to be hypothetically shared are also shared more frequently by actual Twitter users (r = .44; Mosleh, Pennycook, & Rand, 2020). As such, we examine the intent to share these stories on social media.…”
Section: The Present Researchmentioning
confidence: 99%
“…This is particularly relevant with regards to intent to share (mis)information. Although prior work has found that intentions to share are highly correlated with actual sharing on social media (Mosleh et al, 2020), future work should investigate actual online sharing behavior (e.g., Brady et al, 2017). Moreover, because our measures are self-reported, we are not in a position to identify where in the processing stream the bias might be occurring.…”
Section: Limitationsmentioning
confidence: 99%